Mindfulness dalam Pendidikan Anak Usia Dini: Strategi Penguatan Children Well-Being melalui Kesadaran Diri - Dhiya El Quds; Risbon Sianturi; Taopik Rahman (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to examine the role of Mindfulness in early childhood education as a strategy to enhance children's well-being through the development of self-awareness. The method used in this study is a literature review by analyzing various relevant scientific articles from national and international journals. The findings indicate that the implementation of Mindfulness has a positive contribution to children's emotional and social development, particularly in improving emotional regulation, concentration, and self-awareness. In addition, Mindfulness practices help children reduce stress and develop more adaptive responses to their environment. The implementation of Mindfulness in learning can be carried out through simple activities such as breathing exercises, reflection, and body awareness-based games. Therefore, Mindfulness can be an effective approach to support children's well-being holistically in early childhood. This study recommends that educators integrate Mindfulness practices into learning activities to create a healthier learning environment and support optimal child development